Mesh manipulation for local structural property tailoring of medical warp-knitted textiles. (April 2022) - Mueller, Kilian Maria Arthur; Mulderrig, Shane; Najafian, Sara; Hurvitz, Samuel Benjamin; Sodhani, Deepanshu; Mela, Petra; Stapleton, Scott Edward
Abstract: Medical meshes are used as structural reinforcement both in clinical surgery and tissue engineering. However, complex loading conditions often found in such applications result in a non-homogenous stress distribution, for which the uniform reinforcement provided by the meshes is not optimal. This study aims to design a textile reinforcement with a spatially heterogeneous, load-tailored fiber architecture. To this end, we developed a simple method of manipulating a standard uniform mesh by stretching in warp and weft directions to various extents in order to control fiber orientation and fiber volume fraction. Subsequent thermal treatment locked the manipulated configurations allowing further use of the meshes. Firstly, samples in five uniform configurations (two manipulated longitudinally (warp direction), two manipulated transversely (weft direction), one non-manipulated) were obtained and analyzed regarding their morphology as well as their mechanical properties under cyclic uniaxial loading. Significant effects of the manipulation on key characteristics of the pores such as angles, side lengths, aspect ratios, and fiber volume fraction were shown. Tensile testing demonstrated the range of tensile properties achievable with the simple manipulation of the mesh, not only in magnitude but also in the shape of the stress-strain response curve. Finally, local manipulation combining different mesh configurations was exemplarily applied to create a spatially heterogeneous load-tailored reinforcement to match local strain directions in tissue-engineered tubular heart valves. The proposed method enables the use of well-established uniform medical meshes to produce load-tailored non-uniform mesh reinforcement for many applications in an easy-to-implement manner. Graphical abstract: Image 1 Highlights: Uniform biomedical meshes were manipulated in warp and weft direction to alter their pore geometry. Manipulated mesh configurations featured significantly different mechanical behavior. Combing local manipulations creates heterogeneous load-tailored reinforcements.